2008
DOI: 10.1111/j.1365-2249.2008.03707.x
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear factor kappa-B pathway in airway epithelium regulates neutrophil recruitment and host defence following Pseudomonas aeruginosa infection

Abstract: SummaryPseudomonas aeruginosa pneumonia usually results from a deficit of the innate immune system. To investigate whether inflammatory signalling by airway epithelial cells provides a pivotal line of defence against P. aeruginosa infection, we utilized two separate lines of inducible transgenic mice that express a constitutive activator of the nuclear factor kappa-B (NF-kB) pathway (IKTA) or a dominant inhibitor of NF-kB (DNTA) in airway epithelial cells. Compared with control mice, IKTA mice showed an enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…6a) that is involved in chemotaxis of neutrophils may also be due to higher ROS production in Fus1 Ϫ/Ϫ mice (32)(33)(34). These data introduce the possibility that increased ROS production in Fus1 Ϫ/Ϫ mice contributes to increased NF-B and mTOR pathway activity, which in turn increases neutrophil recruitment (26,27,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…6a) that is involved in chemotaxis of neutrophils may also be due to higher ROS production in Fus1 Ϫ/Ϫ mice (32)(33)(34). These data introduce the possibility that increased ROS production in Fus1 Ϫ/Ϫ mice contributes to increased NF-B and mTOR pathway activity, which in turn increases neutrophil recruitment (26,27,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 85%
“…Recognition of bacterial lipopolysaccharides by Toll-like receptors (TLRs) induces airway epithelial NF-B activation, which promotes the production of chemokines involved in neutrophil recruitment and activation (25,26). Through this mechanism, engagement of TLRs regulates host defense following infections caused by Acinetobacter baumannii, Pseudomonas aeruginosa, and Mycoplasma pneumoniae (27)(28)(29). Our analysis of NF-B activation in lung tissues of infected animals showed that at 4 hpi with A. baumannii, NF-B was significantly phosphorylated in Fus1 Ϫ/Ϫ mice, whereas no phosphorylation was observed in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of myeloid cells in the production of neutrophil chemokines in response to bacterial lung inflammation is well established (6,35,66). In addition, alveolar endothelial cells are also important for neutrophil recruitment in the lungs in response to LPS challenge (17). Furthermore, recent studies have demonstrated the role of non-bone marrow-derived cells, including respiratory epithelial cells, in regulating neutrophil influx in patients with lung inflammation induced by bacteria and/or their products (18,79).…”
Section: Neutrophilsmentioning
confidence: 99%
“…19,20 To selectively activate IKKb and hence NF-kB in the airway epithelium, hemizygous male mice that contain both transgenes were crossed with homozygous female mice expressing reverse tetracycline transactivator (rtTA) under the control of the CC10 promoter (a gift from Dr. Jeffrey Whitsett). Approximately half of the pups from these matings expressed all three transgenes, thereby enabling the activation of NF-kB in the airway epithelium after treatment with doxycycline (Dox).…”
Section: Mouse Modelsmentioning
confidence: 99%